Abortion in the Perspective of Islamic Law and Health Law - Ahdiana Yuni Lestari; Agesti Andriani; Dakum Dakum; Setiyawan Gunardi (Universitas Muhammadiyah Purwokerto, 2024)
Free association is a primary factor that has been observed to significantly influence the rate at which abortion practices are being carried out among teenagers. In Indonesia, the rate of abortion cases was reported to be around 2.5 million, among which 1.5 million were carried out by teenagers due to reasons such as pregnancy outside marriage, conception as a result of rape, or life-threatening cases. Therefore, this study aims to thoroughly examine the perspective of Islamic law and health law related to abortion cases. In order to effectively achieve the stated objective, a normative legal analysis was carried out using the Qur’an, Law Number 1 of 2023, Law Number 17 of 2023, PP Number 28 of 2024, PP Number 61 of 2014, MUI Fatwa Number 4 of 2005, MUI Fatwa Number: 1/MUNAS VI/MUI/2000, fiqh 5 madzhab, as well as the results of previous studies published in journals and other references related to the problem. The analysis results were subsequently examined prescriptively by providing legally correct arguments against legal facts or events. The obtained results showed that abortion permitted according to Islamic law were only spontaneous cases (al-isqathal-dzaty), namely the fetus is miscarried naturally and abortion due to life-threatening emergencies (al-isqath al-darury/al-ilajiy). According to health law, abortion was permitted if there were indications of a medical emergency in the pregnant woman or if pregnancy was a result of rape. The permission to perform an abortion must be given by medical personnel and health workers who have the competence and authority, and the act must be carried out in health service facilities that meet the requirements determined by the Minister of Health. Furthermore, the pregnant woman and her husband must also grant an approval, except in cases where the woman is a victim of rape. This is as stated in Article 61 of Law Number 17 of 2023, Article 116 PP number 28 of 2024, Article 31, Article 35 paragraph (2) of PP Number 61 of 2014, Article 463 paragraph (2), and Article 465 paragraph (3) of Law Number 1 of 2023.Keywords: Abortion, Health Law, Islamic Law